Sediment quality of a Ramsar site assessed by chemical and ecotoxicological approaches - Araujo, G. S. [UNESP]; Cruz, A. C.F. [UNESP]; Gusso-Choueri, P. K. [UNESP]; Saint'Pierre, T. D.; Hauser-Davis, R. A.; Martins, C. C.; Abessa, D. M.S. [UNESP] (Elsevier, 2020)
The sediment quality of the Protected Cananéia-Iguape-Peruíbe Area (APA-CIP), listed as one of the Wetlands of International Importance (Ramsar Site), was assessed through geochemical and ecotoxicological analyses, in order to determine if organic and inorganic contaminants retained in the sediments were bioavailable to benthic organisms and could trigger negative effects. Lethal (Tiburonella viscana) and sublethal (Lytechinus variegatus and Nitokra sp.) ecotoxicological endpoints were assessed, as well as sediment texture and organic and inorganic contaminants in sediments obtained at six stations distributed along the APA-CIP. Sites under the influence of the maximum turbidity zone and close to the main local urban center (Cananéia city) presented the worst environmental conditions, indicated by sediment toxicities and high contaminants levels. These conditions may be associated to fine-grained sediments. Metal (Pb, Co, Ni and Zn) concentrations exceeded the regional Sediment Quality Guidelines (SQGs) at stations PT and PM, while Pb also exceeded the Canadian Interim Marine Sediment Quality Guidelines (ISQGs). Total Aliphatic Hydrocarbons (AH) were close to threshold sediment contamination values at PT (maximum turbidity zone). These findings indicate that metals from former mining activities reach APA-CIP, in addition to contaminants from local sources (urban centers, docks, fishing wharfs). Contaminants accumulate in low energy regions, where fine particle and organic matter contents are high. Toxicities appeared to be associated to contaminants, suggesting that the multiple local anthropogenic sources can produce ecological risks, indicating the need for multiple efforts to control external and internal contamination sources in this protected estuarine area.
Keywords: Lytechinus variegatus; Metals; Nitokra sp.; Sediments; Tiburonella viscana; Toxicity